Do ginger footbaths improve symptoms of insomnia more than footbaths with warm water only? – A randomized controlled study. (August 2022) - Kuderer, Silja; Vagedes, Katrin; Szöke, Henrik; Kohl, Matthias; Joos, Stefanie; Gündling, Peter W.; Vagedes, Jan
Abstract: Objectives: To compare the effects between warm water (WW) and ginger footbaths (WW+ginger) on sleep quality and warmth regulation in adults with self-reported insomnia symptoms. Methods: A prospective randomized-controlled study in which 28 participants (mean age 50.9 years, 64.3% women, insomnia symptom duration 11.4 years) were randomized to receive WW ( n = 13) or WW+ginger ( n = 15) daily for 2 weeks. Treatment involved nightly footbaths (12 liters of 38–42 °C warm tap water, maximum duration 20 min) with and without topical ginger (80 g of powdered ginger rhizomes). Main outcome measures: The primary outcome measure was self-reported sleep quality (global score from Pittsburgh Sleep Quality Index, PSQI) at 2 weeks. Secondary outcomes included measures of insomnia severity (Insomnia Severity Index, ISI) and warmth regulation (Herdecke Warmth Perception Questionnaire, HWPQ and 24-hour distal-proximal skin temperature gradient, DPG). Results: WW+ginger had no greater effect on PSQI (mean between -difference 0.0 [95% CI −3.0 to 2.9], Cohen's d =0.0) or ISI (−0.2 [−3.9 to 3.4], 0.0) than WW. Nor were there any significant differences in HWPQ perceived warmth (0.1 ≥ d ≥0.5) or DPG (0.1 ≥ d ≥0.4) between WW and WW+ginger. Both groups improved over time in PSQI (WW+ginger: d =0.7, WW: d =1.3) and ISI (WW+ginger: d =0.8, WW: d =1.0). Perceived warmth of the feet increased only in WW+ginger over time ( d =0.6, WW: d =0.0). Conclusions: This dose of ginger (6.67 g/liter) did not have greater effects on sleep quality, insomnia severity or warmth regulation than WW. Considering effect sizes, costs and risks, the use of WW would be recommended over WW+ginger in this patient population. Highlights: Warm water footbaths with and without topical ginger improved insomnia symptoms. Topical ginger was no more effective than warm water in improving insomnia symptoms. Sleep quality and insomnia severity improved in both groups over time. The distal-proximal skin temperature gradient did not change over time. Perceived warmth of the feet increased only with topical ginger over time.